1997
DOI: 10.1093/emboj/16.18.5509
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin-like protein Smt3p is activated for conjugation to other proteins by an Aos1p/Uba2p heterodimer

Abstract: Smt3p and SUMO-1 contain Ub-like domains with much less sequence similarity to Ub than among genuine Ub SMT3 is an essential Saccharomyces cerevisiae gene homologs. Most of these, including the S.cerevisiae encoding a 11.5 kDa protein similar to the mammalian nucleotide excision repair protein Rad23p (Watkins et al., ubiquitin-like protein SUMO-1. We have found that 1993) and Dsk2p, involved in spindle pole body duplicSmt3p, like SUMO-1 and ubiquitin, can be attached ation (Biggins et al., 1996), do not become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
421
0
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 491 publications
(443 citation statements)
references
References 53 publications
14
421
0
6
Order By: Relevance
“…The same procedure was used to purify the following point mutants as single subunits: Slx5-7 (C556S), Slx5-8 (C556S, H558A, C561S), Slx8-2 (C221S), Slx8-3 (C221S, H223A, C226S). The sumoylation enzymes His6-Aos1/Uba2, His6-Ubc9, and HF-Smt3 were purified from plasmids generously provided by Erica Johnson using published methods [37,38].…”
Section: Expression and Purification Of Recombinant Proteinsmentioning
confidence: 99%
“…The same procedure was used to purify the following point mutants as single subunits: Slx5-7 (C556S), Slx5-8 (C556S, H558A, C561S), Slx8-2 (C221S), Slx8-3 (C221S, H223A, C226S). The sumoylation enzymes His6-Aos1/Uba2, His6-Ubc9, and HF-Smt3 were purified from plasmids generously provided by Erica Johnson using published methods [37,38].…”
Section: Expression and Purification Of Recombinant Proteinsmentioning
confidence: 99%
“…In mammalian cells, there are three SUMO genes, whereas only a single gene, smt3, exists in Drosophila (Huang et al, 1998;Johnson et al, 1997;Su and Li, 2002), making Drosophila a useful experimental system in which to study the biological functions of sumoylation. Several studies in Drosophila have suggested different functions of sumoylation, including in the regulation of cell signaling during development and ecdysteroid biosynthesis, but their underlying mechanisms remain largely unclear (Miles et al, 2008;Nie et al, 2009;Talamillo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…To confirm that the detection of GFP-SUMO-1 in the nucleolus corresponds to the presence of modified proteins, HeLa cells were transfected with GFP-SUMO-1⌬6. This mutant form of SUMO-1 lacks the C-terminal Gly-Gly motif and therefore cannot be conjugated to substrates (Johnson et al, 1997). Western blot analysis using antibodies against GFP shows that GFP-SUMO-1⌬6 is detected as a single band of the expected size ( Figure 1B, arrow), whereas full-length GFP-SUMO-1 is detected as a high-molecular-weight smear of conjugated products, indicating that this GFP fusion protein is effectively conjugated.…”
mentioning
confidence: 99%